Instructional Supports for Motivation Trajectories in Introductory College Engineering - Kristy A. Robinson; Amalia Krystal Lira; S. Patrick Walton; Daina Briedis; Lisa Linnenbrink-Garcia (SAGE Publishing, 2022)
Students, instructors, and policy makers are in need of research-based recommendations for supporting students' motivation to pursue STEM fields. The present study addressed this need by examining relations between perceived motivational supports, year-long trajectories of expectancy for success and three task values, and grades among students ( N = 1,021) in a large, gateway engineering course. Results indicated that students with higher motivation at the beginning of the year tended to perceive their class as more motivationally supportive. Controlling for relations between initial motivation and perceptions, perceived instructional supports for mastery goals, autonomy, and competence predicted more positive trajectories of all three task values. Conversely, higher perceived instructor performance goals negatively predicted grades and the slopes of self-efficacy and interest value. Results contribute key understanding about the interconnectedness of individual motivation and climate perceptions, while indicating the importance students place on certain motivationally supportive practices in promoting students' STEM motivation trajectories.